2020
DOI: 10.3390/jcm9082643
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression of Transient Receptor Potential Channels in Peripheral Blood Mononuclear Cells of Inflammatory Bowel Disease Patients

Abstract: We examined the expression profile of transient receptor potential (TRP) channels in peripheral blood mononuclear cells (PBMCs) from patients with inflammatory bowel disease (IBD). PBMCs were obtained from 41 ulcerative colitis (UC) patients, 34 Crohn’s disease (CD) patients, and 30 normal subjects. mRNA levels of TRP channels were measured using the quantitative real-time polymerase chain reaction, and correlation tests with disease ranking, as well as laboratory parameters, were performed. Compared with cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…In addition, administration of CB2 agonists or PAR-2 antagonist to mice with inflammatory pain or with knee joint pain led to the reduction of NLRP3 inflammasome activation [ 37 , 38 ]. Previous studies have widely described the sensitization of these nociceptor pathways in gastrointestinal inflammation by immune mediators [ 39 , 40 , 41 , 42 ]. Specifically, our data indirectly indicate that the inflammasome pathway can also regulate the expression of these mucosal nociceptors and their subsequent effect on visceral pain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, administration of CB2 agonists or PAR-2 antagonist to mice with inflammatory pain or with knee joint pain led to the reduction of NLRP3 inflammasome activation [ 37 , 38 ]. Previous studies have widely described the sensitization of these nociceptor pathways in gastrointestinal inflammation by immune mediators [ 39 , 40 , 41 , 42 ]. Specifically, our data indirectly indicate that the inflammasome pathway can also regulate the expression of these mucosal nociceptors and their subsequent effect on visceral pain.…”
Section: Discussionmentioning
confidence: 99%
“…Using PBMCs obtained from a different cohort of patients with IBD (Table S1 ) [ 24 ], we evaluated LRG mRNA levels in patients with IBD. Blood samples (10 mL) were obtained by cubital venous puncture and collected in standard sterile polystyrene vacuum tubes with heparin.…”
Section: Methodsmentioning
confidence: 99%
“…Transient Receptor Potential Melastatin-8 (TRPM8) is a non-selective cation channel activated by cold temperature and by cooling agents, and a neuronal sensor that plays a role in cold and mechanical allodynia associated with neuropathic pain secondary to trauma. It was proved that this channel is involved in pain perception, and that TRPM8 activation or deactivation can modulate analgesia [114]. De Petrocellis demonstrated in his paper that CBG is the second most efficient TRPM8 antagonist, and he found that a "CBG-free" extract from the Cannabis plant (with the exact quantity of CBG that was extracted from the plant) was inactive per se, but when added to pure CBG, the activity of the CBG-enriched extract was significantly increased, and it was more efficient in antagonizing TRPM8 than pure CBG.…”
Section: Cannabigerol (Cbg)-type Compoundsmentioning
confidence: 99%